2011
DOI: 10.1371/journal.pone.0027597
|View full text |Cite
|
Sign up to set email alerts
|

Do Patterns of Bacterial Diversity along Salinity Gradients Differ from Those Observed for Macroorganisms?

Abstract: It is widely accepted that biodiversity is lower in more extreme environments. In this study, we sought to determine whether this trend, well documented for macroorganisms, also holds at the microbial level for bacteria. We used denaturing gradient gel electrophoresis (DGGE) with phylum-specific primers to quantify the taxon richness (i.e., the DGGE band numbers) of the bacterioplankton communities of 32 pristine Tibetan lakes that represent a broad salinity range (freshwater to hypersaline). For the lakes inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
81
2
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(97 citation statements)
references
References 70 publications
6
81
2
4
Order By: Relevance
“…Dex80-37, was only very distantly related to BC3 (87% sequence identity) and affiliates differently within the Flavobacteriaceae/Bacteriales/Sphingobacteriaceae branch ( Figure 6). Database searches indicated that sequences very closely related (ore even identical) to BC3 were retrieved in the NGS study of the Santa Pola salterns mentioned above (Ghai et al, 2011), as well as in other studies from hypersaline environments worlwide, such as in Lake Chaka (China), Chula Vista salterns (California, USA), Lake Tyrrel (Australia) and Lake Aran-o-Bidgol (Iran) (Jiang et al, 2007;Wang et al, 2011;Podell et al, 2013). However, in none of these studies there is an explicit reference to this group nor is its ubiquity acknowledged.…”
Section: Resultsmentioning
confidence: 88%
“…Dex80-37, was only very distantly related to BC3 (87% sequence identity) and affiliates differently within the Flavobacteriaceae/Bacteriales/Sphingobacteriaceae branch ( Figure 6). Database searches indicated that sequences very closely related (ore even identical) to BC3 were retrieved in the NGS study of the Santa Pola salterns mentioned above (Ghai et al, 2011), as well as in other studies from hypersaline environments worlwide, such as in Lake Chaka (China), Chula Vista salterns (California, USA), Lake Tyrrel (Australia) and Lake Aran-o-Bidgol (Iran) (Jiang et al, 2007;Wang et al, 2011;Podell et al, 2013). However, in none of these studies there is an explicit reference to this group nor is its ubiquity acknowledged.…”
Section: Resultsmentioning
confidence: 88%
“…In a study of soils and lake sediments associated with a hypersaline lake in Texas, moderate declines in richness were observed along a salinity gradient (67). However, increasing salinity has more commonly been shown to either have no effect on total richness (68, 69) or decrease overall phylogenetic diversity while promoting higher diversity within a few specific lineages (29,70,71). Therefore, our results are contrary to the results found in most other studies, suggesting that microbial diversity may be significantly constrained by high salinity only when communities also experience other stressors or resource limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Soil salinity can also lead to high internal levels of ions that are toxic to metabolic activities (27) and can denature the extracellular enzymes necessary for carbon and nutrient acquisition. Thus, increased salinity represents a biological stress that requires evolutionary or energetically expensive solutions, has been shown to be an important determinant of microbial community composition in other systems (28,29), and creates additional stress for biological life in MDV soils.…”
mentioning
confidence: 99%
“…Increasing salinity was found to be correlated with a reduced richness of plant and animal species (5,6) and of microbial community diversity in some cases (7,8). However, this pattern is not consistently observed for all microbial communities (9)(10)(11)(12)(13)(14). A better understanding of the taxonomic composition and diversity of microbial communities in saline lakes and the mechanisms that govern the community structure is a long-standing goal and challenge for microbial community ecologists (15)(16)(17).…”
mentioning
confidence: 99%